Perilaku kekasaran permukaan baja AISI 1045 terhadap kekerasan dan laju korosi serta daya lekat permukaan hasil elektroplating - Sunardi Sunardi; Slamet Wiyono; Dhimas Satria; Rina Lusiani; Erny Listijorini; Wira Pratama (TURBO [Tulisan Riset Berbasis Online], 2020)
Electroplating is the coating metals with thin layers of other metals by electrolysis to improve the surface properties of materials, especially corrosion resistance. Electroplating is widely used in the automotive, electronics, medical, aerospace, gas, and oil industries. This study will discuss the effect of substrate surface roughness of AISI 1045 steel toward surface roughness, hardness, corrosion rate, and bonding strength of the coating. The surface roughness of the substrate is obtained by grinding process using sandpaper with grades 80, 320, and 1000. In this study, the coating material is Chromium. The electroplating parameters used in this research are 5-volt voltage, current 500 Amperes, and the time of 15 minutes. From this research, it is known that the surface roughness of the substrate material has an influence on the quality of the coating. The lower the surface roughness, improve the roughness, hardness, corrosion rate, and bonding strength.Keywords: electroplating, surface roughness, hardness, corrosion rate, bonding strength.